2021
DOI: 10.1007/s12031-021-01827-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treponema denticola Infection Induces Aβ1–40 and Aβ1–42 Accumulation in the Hippocampus of C57BL/6 Mice

Abstract: Accumulation of amyloid-β (Aβ) in the brain is a central component of pathology in Alzheimer's disease.A growing number of evidences demonstrate close associations between periodontal pathogens including Porphyromonas gingivalis (P. gingivalis) and Treponema denticola (T. denticola) and AD. However, the effect and mechanisms of T. denticola on accumulation of Aβ remain to be unclear. In this study, we demonstrated that T. denticola was able to enter brain and act directly on nerve cells resulting in intra and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…It has been clarified that BBB breakdown is always associated with cognitive decline and AD [ 99 ]. Despite the strong evidence from laboratory-based research [ 8 , 90 ] and the histopathological observations [ 6 ], the role of periodontal spirochaetes, and indeed P. gingivalis , in the pathogenesis of AD is widely underappreciated among the scientific community. The synergism between T. denticola and P. gingivalis in the oral subgingival dysbiotic biofilm may enable the former to regain its motility and move along the neural cells in the surrounding disrupted periodontal tissue via proprioceptors and the trigeminal free nerve endings.…”
Section: Discussion and Implications For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been clarified that BBB breakdown is always associated with cognitive decline and AD [ 99 ]. Despite the strong evidence from laboratory-based research [ 8 , 90 ] and the histopathological observations [ 6 ], the role of periodontal spirochaetes, and indeed P. gingivalis , in the pathogenesis of AD is widely underappreciated among the scientific community. The synergism between T. denticola and P. gingivalis in the oral subgingival dysbiotic biofilm may enable the former to regain its motility and move along the neural cells in the surrounding disrupted periodontal tissue via proprioceptors and the trigeminal free nerve endings.…”
Section: Discussion and Implications For Future Researchmentioning
confidence: 99%
“…This oral spirochete can enter the brain and it has been detected in the trigeminal ganglia and in the hippocampus [ 6 ]. An experimentally induced infection of the oral cavity with T. denticola demonstrated the release of Aβ 1–40 and Aβ 1–42 from its parent protein (amyloid precursor protein) due to the activation of β-secretase and γ secretase [ 90 ] and resulted in the promotion of GSK-3β activation and tau phosphorylation [ 8 ].…”
Section: Could the Trigeminal Nerve Pathway Act As The Entrance For ...mentioning
confidence: 99%
“…The role of T. denticola in cognitive function has not been studied as much as P. gingivalis . Su et al (2021) demonstrated that T. denticola could enter the brain, act directly on nerve cells, and result in intra- and extracellular Aβ 1-40 and Aβ 1-42 accumulation in the hippocampus of C57BL/6 mice [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 report revealed T. denticola as a potential contributing factor, along with P. gingivalis , as risk factors for AD. The research group found that T. denticola had the ability to enter the brain and increased the expression of amyloid-β (the hallmark in AD), although the mechanism is unclear [ 66 ].…”
Section: Health Issues Affecting Alzheimer's Diseasementioning
confidence: 99%